Laser-assisted printing of electrodes using metal–organic frameworks for micro-supercapacitors - Zhang, Wang (2022)
Direct laser scribing, an advanced printing technique, has been recently developed to enable the carbonization of carbonaceous precursors in a rapid, precise, and cost-effective manner. Herein, it is reported that metal−organic frameworks (MOFs) can be converted into patterned derived carbon with desired structural features using a CO2 infrared laser system. Metal species in MOFs play a key role in the morphology, porous structure, and crystallinity of the resulting laser-induced products by studying six representative MOFs. Diverse features such as ordered porous structure and continuous network microstructure can be obtained in the laser-induced MOF-derived carbon, which is influenced by the melting and boiling points of metals and their magnetic and catalytic behaviors. Furthermore, a core–shell structured composite (MOF-199@ZIF-67) has been designed and prepared for the fabrication of 12-interdigital electrodes derived from the composite by laser-assisted printing. The as-obtained electrodes with highly porous and hierarchical structure show an enhanced specific capacitance for micro-supercapacitors (MSCs). This work provides a complementary heat treatment method to produce MOF-derived carbon nanomaterials with desired structural features and patterns for MSCs and micro-device-related applications.